2003
DOI: 10.1016/j.jacc.2003.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Nebivolol and its 4-keto derivative increase nitric oxide in endothelial cells by reducing its oxidative inactivation

Abstract: In conclusion, the findings of the present study indicate that nebivolol increases NO also by decreasing its oxidative inactivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
2
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 39 publications
4
42
2
4
Order By: Relevance
“…Moreover, reactive oxygen radicals were reduced in a model with hypercholesteremic rabbits by reducing O 2- [25,27] in the vessel wall. Nebivolol possesses several antioxidative characteristics, it directly interacts with reactive oxygen radicals [24,25]. In a rat model of angiotensin II-mediated hypertension it could be shown that nebivolol induced a dissociation of p67 (phox) and Rac1, and additionally an inhibition of NADPH oxidase activity in rat heart membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, reactive oxygen radicals were reduced in a model with hypercholesteremic rabbits by reducing O 2- [25,27] in the vessel wall. Nebivolol possesses several antioxidative characteristics, it directly interacts with reactive oxygen radicals [24,25]. In a rat model of angiotensin II-mediated hypertension it could be shown that nebivolol induced a dissociation of p67 (phox) and Rac1, and additionally an inhibition of NADPH oxidase activity in rat heart membranes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to salt sensitivity, the 4a/b polymorphism has been shown to determine the efficacy of nevibolol, a betablocker that in addition increases the production of NO. [44][45][46][47] Nebivolol is known to increase NO levels 46 possibly by inhibiting NO oxidation. 47 Nebivolol improved left ventricular hypertrophy and endothelial dysfunction in subjects carrying the b/b eNOS genotype, but failed to do so in those with the 4a/b genotype.…”
Section: Ethnicity and Enos Polymorphismsmentioning
confidence: 99%
“…[44][45][46][47] Nebivolol is known to increase NO levels 46 possibly by inhibiting NO oxidation. 47 Nebivolol improved left ventricular hypertrophy and endothelial dysfunction in subjects carrying the b/b eNOS genotype, but failed to do so in those with the 4a/b genotype. 45 The diminished production of NO reported in subjects with the 4a/b mutation may prevent the beneficial effects of nebivolol.…”
Section: Ethnicity and Enos Polymorphismsmentioning
confidence: 99%
“…Endothelial dysfunction in the brachial artery is related to the presence of endothelial dysfunction in the coronary arteries; while it is a predictor of cardiovascular events in patients with CAD. 13) Endothelial function measured by means of flow-mediated dilatation (FMD) of the brachial artery is also significantly impaired in patients with SCF.…”
Section: Discussionmentioning
confidence: 99%